2020
DOI: 10.1038/s41598-020-64767-x
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiological study of the rotavirus VP8* protein from different P genotypes in Valencia, Spain

Abstract: The aims of the present work were to determine the prevalence and titer of serum antibodies against several rotavirus VP8* proteins from different P genotypes in children and adults in Valencia, Spain; and to determine the role of the secretor status (FUT2 G428A polymorphism) in the antibody response. The VP8* protein from the P[4], P[6], P[8], P[9], P[11], P[14] and P[25] genotypes were produced in E. coli. These proteins were tested with 88 serum samples from children (n = 41, 3.5 years old in average) and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In RV, resistance to infection appears to be genotype-dependent, is mediated mainly by histo-blood group antigens (HBGAs) [ 38 , 39 ] and could be conditioned by microbiota composition [ 40 ]. For over 30 years, sialic acid was considered the glycoside receptor of animal RVs, yet human strains were considered independent from sialic acid [ 41 ]. The recently discovered role of HBGAs as potential receptors has significantly advanced understanding of RV diversity, evolution and epidemiology.…”
Section: Hbgas As Viral Receptors and Their Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In RV, resistance to infection appears to be genotype-dependent, is mediated mainly by histo-blood group antigens (HBGAs) [ 38 , 39 ] and could be conditioned by microbiota composition [ 40 ]. For over 30 years, sialic acid was considered the glycoside receptor of animal RVs, yet human strains were considered independent from sialic acid [ 41 ]. The recently discovered role of HBGAs as potential receptors has significantly advanced understanding of RV diversity, evolution and epidemiology.…”
Section: Hbgas As Viral Receptors and Their Implicationsmentioning
confidence: 99%
“…The precursor consists of a galactose molecule (Gal) bound to an N-acetylglucosamine molecule (GlcNAc) that form a disaccharide. Depending on the bond that joins both sugars, the precursors are classified into two different groups: type I (link β-1,3) or type II (link β-1,4) [ 41 ]. Secretor status is determined by the FUT 2 gene, which encodes for galactosidase 2 alpha-fucosyltransferase (adds a fucose residue in the α-1,2 position of the Gal residue), where non-secretors lack functionality in that enzyme and are consequently unable to express the H antigen [ 41 ].…”
Section: Hbgas As Viral Receptors and Their Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated rotavirus-specific antibody titers in adults in association with secretor status [9,[35][36][37][38]. All of these studies have shown that secretors have higher serum rotavirus IgG titers, as well as higher neutralization antibody titers against the predominant strains in the study population (mostly P [8]).…”
Section: Secretor Status and Levels Of Maternal Rotavirus Immunoglobulinsmentioning
confidence: 99%
“…Although some discrepancies have been found, most reports have shown that positive secretor status was strongly associated with susceptibility to P [8] and P [4] genotypes [36,41,42]. As for serological studies, higher RV-specific immunoglobulin G (IgG) titres in serum and IgA titres in saliva have been reported in secretors compared to non-secretors [43][44][45][46]. Higher anti-RV antibody titres reflects a larger number of previous infections, making it an indirect marker of susceptibility.…”
Section: Hbgas and Rvmentioning
confidence: 99%